التفكير الدوكماتي عند طلبة جامعة بغداد (Journal Of Educational and Psychological Researches, 2015)
The world has seen and from our Arab significant changes as a result of scientific progress tremendous Born information revolution circulated individuals around the world via the Internet, have left traces extreme depth on their thinking and attitudes in spite of idiosyncrasies that characterize the communities in terms of their cultural, social and nature of education systems where, However, there were some aspects of transformation and change in various areas of life that had a direct impact on the construction of intellectual individuals, and which is no doubt that human beings look alike in respects morphological and biological see them disagree intellectually, everyone has ideas and values​​, especially distinguish it from others.       This represents a problem in the building society, so what if the exposure of students to this case and in particular they are considered an important segment in any society, reliable in building a promising future, and is the mainstay of development, hence crystallized the problem of current research to find out whether students Aldokmatiownthinkinornot?The importance of research is concentrated in that he addressed the university students who are educated class-conscious, as is the undergraduate stage study important and vital Situated in the educational ladder, and is responsible in the number of frames of human education to supplement the community members are complementary, Thinking Aldokmati have negative consequences on the individual and society, therefore, the scarcity of studies that dealt with Iraq this important segment of society and knowledge level of thinking Aldokmati then make the necessary attention to this aspect and study.                                                                                              Based on the foregoing objectives of the present research identified the following:                                                                      • You know when you think Aldokmati university students.• You know statistically significant differences in thinking Aldokmati when university students according to gender and